Block-wise Authenticated DNA-based Image Encryption with Tamper Localization using HKDF-Derived Keys - Bagus Satrio Waluyo Poetro; Kusworo Adi; Aris Puji Widodo (Journal of Computing Theories and Applications, 2026)
Confidentiality alone cannot establish whether a medical, forensic, cloud-stored, or remotely sensed image has been modified during transmission, while a single global authentication verdict cannot identify the affected region. This paper presents a block-wise authenticated DNA-based image encryption framework that integrates a DNA-chaos confidentiality core with pre-decryption integrity verification and spatial tamper localization. An authenticated ephemeral X25519 key exchange establishes a session secret, which is expanded by HKDF-SHA256 into four transcript-bound, domain-separated subkeys for permutation, DNA operations, diffusion, and authentication. Chaotic seeds are derived from a canonical plaintext hash and block coordinates, preserving strong plaintext differential sensitivity while confining post-encryption modifications to the affected blocks. Ciphertext integrity is enforced using a block-wise encrypt-then-MAC construction with 128-bit truncated HMAC-SHA256 tags that authenticate both the canonical header and each ciphertext block. A reduction-based security argument shows that the authentication layer provides ciphertext integrity and conditionally upgrades an IND-CPA encryption core to IND-CCA security under standard HKDF and HMAC assumptions, while the confidentiality claim remains explicitly conditional on the encryption core. Experiments on 30 tuberculosis chest radiographs across five independent sessions achieved a ciphertext entropy of 7.9972, near-zero adjacent-pixel correlation, 99.61% NPCR, and 33.47% UACI. Across five representative tampering attacks, the proposed framework achieved an observed 100% block-level true-positive rate, 0% false-positive rate, and required only 2.847 ± 0.258 ms for block-wise authentication with 6.25% tag overhead using the default 16×16 block configuration. These results demonstrate that the proposed framework effectively combines statistical confidentiality, modern cryptographic key management, and reliable block-level tamper localization within a unified authenticated image encryption architecture.